Computational commutative and non-commutative algebraic geometry - Cojocaru, Svetlana; Pfister, Gerhard, 1947-; Ufnarovski, Victor (NATO science series. Computer and systems sciences ;, 2005)
This publication gives a good insight in the interplay between commutative and non-commutative algebraic geometry. The theoretical and computational aspects are the central theme in this study. The topic is looked at from different perspectives in over 20 lecture reports. It emphasizes the current trends in commutative and non-commutative algebraic geometry and algebra. The contributors to this publication present the most recent and state-of-the-art progresses which reflect the topic discussed in this publication. Both researchers and graduate students will find this book a good source of inf.